BEBERAPA CATATAN FAUNA EKHINODERMATA DARI PERAIRAN TAPAK TUAN, ACEH SELATAN NANGROE ACEH DARUSSALAM - Yusron, Eddy (UI Scholars Hub, 2003)
Notes On The Echinoderm Fauna Of The Tapak Tuan Bay Waters, Aceh Selatan The Nangroe Aceh Darussalam. A total of 21 species of echinoderms, belonging to of 5 species Holothuroidea, 5 species of Asteroidea, 4 species Echinoidea and 7 species Ophiuroidea have been found in the Tapak Tuan of Aceh Selatan. The Ophiuroidea were relatively dominant in the sea grass zone. On the basis of population density, Ophiuroidea was the dominant group and relatively highest in the individual density. In general, the number of species of echinoderm fauna is smaller than that in the Sekotong Lombok Barat bay waters. The species composition, community structure, zonation, and spatial distribution of echinoderm fauna are discussed in this paper.